DRUG RESISTANCE, VIABILITY AND VIRULENCE IN VITRO ОF MYCOBACTERIUM TUBERCULOSIS STRAINS OF DIFFERENT GENOTYPES - O. A. Manicheva (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The drug resistance, mutation spectrum caused resistance to rifampicin and isoniazid, viability, cytotoxicity were studied as well as 111 clinical isolates of Mycobacterium tuberculosis (MBT) were genotyped. Spoligotyping revealed 28 spoligotypes; the greatest number of strains belonged to genetic families Beijing and LAM. The typing of 59 strains of spoligotype SIT1 (Beijing) allowed to differentiate 19 variants of IS6110-RFLP-profiles: 13 of them were individual and 6 were presented by clusters. The clusters А0 and В0 included the greatest number of M. tuberculosis strains — 21 (35,6%) and 17 (28,8%) accordingly. The high frequency of MLU and SLU of Beijing strains was associated with mutations rpoB Ser531→Leu and katG Ser315→Thr. The strains of M. tuberculosis belonged to another genetic families (T, H, Ural, U) have shown drug resistance more often. The level of resistance to isoniazid in vitro in MLU/SLU strains of MBT of different genotypes, especially, was high in case of mixed mutations such as katG Ser315→Thr и inhA_T15. The rates of viability and cytotoxicity of MBT strains of studied genotypes with different spectrum of mutations and phenotypic drug resistance were not substantially distinguished.